Implementasi Pendidikan karakter di MTs Al-Furqon Melalui Keteladanan dan Pembiasaan - Delina Dwi Sundani; Undang Ruslan Wahyudin; Jaenal Abidin (Universitas Muhammadiyah Enrekang, 2022)
This purpose of this study is to describe various strategies for implementing character education at MTs Al-Furqon through example and habituation. This research is a descriptive study using qualitative methods. This research was conducted at MTs Al-Furqon. The objects of this research is the teacher and student. Data collection techniques used are observation, interviews, and documentation. The result of the study indicate that excemplary and habituation are important things that must be considered in the process of internalizing character values in schools. There are several strategies for implementing character education, such as the habit of dhuha prayer, congregational prayer, and talaqqi of the Qur’an. The implementation of character education cannot be separated from the role of principals, teachers, staff, and students.